Refractory Gestational Trophoblastic Neoplasia: A Novel Drug Combination With Paclitaxel and Carboplatin Produces Durable Complete Remission. Issue 9 (November 2015) - Rathod, Praveen S.; Kundargi, Rajshekar; Pallavi, V.R.; Vijay, C.R.; Devi, Uma K.; Bafna, Uttam D.
Abstract : Objective: The aim of this study was to evaluate the results with novel drug combination consisting of paclitaxel and carboplatin (PC) for salvage of refractory high-risk gestational trophoblastic neoplasia (GTN) previously treated with EMA-CO (etoposide, methotrexate, actinomycin, cyclophosphamide, and vincristine) and EMA-EP (etoposide, methotrexate, actinomycin, and cisplatin) regimens. Study Design: This was a prospective study conducted at a regional cancer institute from 2008 to 2012. The study group received the combination of paclitaxel (175 mg/m 2 ) and carboplatin (area under the curve, 6) intravenously every 3 weeks. After undetectable β-subunit of human chorionic gonadotropin values are achieved, 2 courses of additional chemotherapy were administered to reduce the risk of relapse. They were followed up and assessed by clinical examination, monthly β-subunit of human chorionic gonadotropin for a minimum of 24 months. The event-free survival and overall survival were calculated for all patients using Kaplan-Meier curve (SPSS version 19; SPSS Inc). Results: A total of 65 persistent GTN patients were treated during the study period. Eight (12.3%) of 65 patients having refractory GTN were treated with PC regimen. The initial International Federation of Gynecology and Obstetrics staging in the study group was stage I disease in 1 (12.5%), stage III in 4 (50%), and stage IV in 3 (37.5%) patients. According to the World Health Organization prognostic risk scores, 1 patient was in the low-risk group (12.5%), and 7 patients were in the high-risk group (87.5%). The study group received a total 35 courses of the combination PC. The median number of courses for each patient was 4.4. The complications include mucositis in 3 patients and thrombocytopenia, febrile neutropenia, and transient hepatic dysfunction in other patients. Six (75%) of 8 patients had good response, whereas 2 patients had progression. Five patients (62.5%) are in remission at median 30 months' follow-up, and 3 (37.5%) of 8 patients have died. Conclusion: The combination of paclitaxel and carboplatin (PC) regimen produces durable complete remission and manageable side effect profile in patients with refractory GTN previously treated extensively with frontline chemotherapies.